2018
DOI: 10.1002/ejic.201800793
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Decorated Nanodiamonds: Powerful Multifunctional Materials for Sensing, Imaging, Diagnostics, and Therapy

Abstract: Gold-decorated nanodiamonds is an interesting multifunctional material that can find space in numerous applications in the biological field. The coupling and/or synergy of the properties of the individual components can offer interesting solutions in the field of optical labeling, imaging, molecule and drug delivery, and biosensing. This microreview describes the techniques used for the synthesis of these materials and in- [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 71 publications
(86 reference statements)
2
8
0
Order By: Relevance
“…Additionally, it was found that combining Au with ND prevents Au nanostructure from degradation during photoacoustic imaging 28 . The same was observed with transmission electron microscopy (TEM) imaging 10 . Another synergy effect, the catalytic and sensor facilities are based on charge transfer process found only in the hybrid system 10 .…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…Additionally, it was found that combining Au with ND prevents Au nanostructure from degradation during photoacoustic imaging 28 . The same was observed with transmission electron microscopy (TEM) imaging 10 . Another synergy effect, the catalytic and sensor facilities are based on charge transfer process found only in the hybrid system 10 .…”
Section: Introductionsupporting
confidence: 59%
“…Combining Au with porous silica 2 , silicon 3 , iron oxides 4 , polymers 5 or other organic macromolecules, e.g. transition metals complexes 6 , different kinds of carbon nanomaterials 7 10 etc., have been described previously.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…DNDs have exceptional physiochemical properties and present a broad range of potential applications in nanotechnology research [21][22][23][24][25][26]. Moreover, this nanomaterial exhibits great potential as a green catalyst in itself, or as catalyst support for a variety of chemical reactions [27].…”
Section: Introductionmentioning
confidence: 99%